Optimisation of InGaAsP quantum well cells for hybrid solar-thermophotovoltaic applications - Rohr, C. (Institutional Knowledge at Singapore Management University, 1999)
We discuss quantum well cells (QWCs) in the quaternary system In1-xGaxAsyP1-y lattice-matched to the InP substrate (x approximate to 0.47y) for the use in solar and thermophotovoltaic (TPV) applications. The deep lattice-matched wells of up to y = 1 (In0.53Ga0.47As) can be incorporated without any strain. The effective band-gap for absorption in these quaternary QWCs can be tailored (up to similar to 1.7 mu m) to produce the ideal band-gap for a given blackbody or selective-emitter spectrum while retaining a comparatively high efficiency for the solar spectrum. This has a great potential for higher-efficiency cells, especially for hybrid solar-TPV applications. We present the results of a new model for the external quantum efficiency of InGaAsP QWCs. The model calculates the spectral response of multi-layer InGaAsP photovoltaic cells with and without quantum wells. It is in very good agreement with the experimental spectral response of InGaAsP QWCs with a variety of designs and therefore is an important tool for the optimisation of these cells. Besides improvements in quantum well geometry, processing and material quality the high efficiencies we obtain can be even further increased by additional features such as the use of back surface reflectors. We also investigate how these cells perform under several different illuminations such as solar and blackbody spectra as well as narrow-band selective-emitter spectra from erbia and ytterbia comparing them to lattice-matched InGaAs monolithic interconnected modules. We conclude that the InGaAsP QWC system is a very promising candidate for high-efficiency photovoltaic cells for hybrid solar-TPV applications.